Effectiveness of Diets Incorporating Nano-Zeolite and Urea-Impregnated Nano-Zeolite on Fermentation Efficiency in Rumen Fluid In Vitro - Dede Kardaya; Pia Nurmala Dewi; Deden Sudrajat; Dewi Wahyuni; Ikhsan Qodri Pramartaa; Ruslan Abdul Gopar; Windu Negara; Raden Siti Nurlaela (Indonesian Journal of Applied Research (IJAR), 2025)
Zeolite had been widely investigated in animal feed for its ability to improve feed efficiency and reduce ammonia emissions, and nano-zeolite offered greater adsorption capacity due to its expanded surface area. This study evaluated the effects of nano-zeolite supplementation on ammonia (NH₃), volatile fatty acids (VFA), the VFA/NH₃ ratio, and pH during in vitro rumen fermentation. A two-factor randomized block design (6 × 6) with four replicates was used. Incubation time (2, 4, 8, 12, 24, and 48 h) served as the first factor, and six dietary treatments served as the second factor: control, urea-supplemented concentrate, inactivated nano-zeolite, activated nano-zeolite, urea-impregnated inactivated nano-zeolite, and urea-impregnated activated nano-zeolite. Nano-zeolite, whether active or urea-impregnated, did not significantly improve rumen fermentation efficiency based on NH₃, VFA, or VFA/NH₃ ratio. All nano-zeolite diets performed similarly to the control and urea-only diets. Fermentation efficiency peaked at 4 and 8 hours of incubation, indicating that nano-zeolite combined with urea supported stable fermentation, particularly during early to mid-incubation.